The implications of the exceptional measures adopted by the Algerian monetary authorities in the shadow of the Covid-19 pandemic on the Algerian banking system - yahiaoui, mohamed (Journal of Research in Finance and Accounting, 2021)
This research aims to present the content of the exceptional measures adopted by the Algerian monetary authorities after the outbreak of the Covid-19 pandemic, in particular those related to the banking sector, and their implications for the banking system, whether in terms of liquidity, credit activity and financial solvency. Among the results obtained: The decrease in the minimum capital adequacy will lead to an increase in banks' lending activity, which may eventually lead to a possible increase in bad debts. Modifying some monetary policy tools will also improve bank liquidity levels and allow banks to meet funding requests from defaulting customers due to this pandemic.The need to improve credit and liquidity risk management mechanisms in accordance with Basel III recommendations .